Venous thromboembolism in pediatric trauma patients: Ten‐year experience and long‐term follow‐up in a tertiary care center. Issue 8 (9th January 2017) - Leeper, Christine M.; Vissa, Madhav; Cooper, James D.; Malec, Lynn M.; Gaines, Barbara A.
Abstract: Background: Pediatric trauma patients are at high risk for development of venous thromboembolism (VTE). Our objective is to describe incidence, risk factors, and timing of development of VTE, anticoagulation complications, and long‐term VTE outcomes in a critically injured pediatric population. Procedure: We did a retrospective review of pediatric (0–17 years) trauma admissions to intensive care unit from 2005 to 2014. Our center employs VTE screening and prevention protocols for high‐risk patients based on hypercoagulable history, age, injuries, and medical interventions. We collected demographics, VTE prevention measures, VTE incidence, therapeutic anticoagulant use, and outcomes including postthrombotic syndrome (PTS) and clot resolution. Analysis included Wilcoxon rank–sum, Fisher exact, and logistic regression modeling. Results: Seven hundred fifty‐three subjects were analyzed. No patients on chemical prophylaxis (21/753) developed VTE. Overall incidence of deep vein thrombosis (DVT) was 8.9%; pulmonary embolism (PE) was 0%. Time to diagnosis was median (interquartile range [IQR]) 10.5 (6.5–14.5) days, with 63% of clots being symptomatic. Risk factors for VTE development included severe traumatic brain injury (TBI), acute traumatic coagulopathy (defined by elevated admission international normalized ratio), age less than or equal to 3 or age 13 years or more, injury severity, and child abuse mechanism. At a median (IQR) follow‐up of 13 (6–19) months, 52.1% had persistent clot and 15.8% had PTS. Therapeutic anticoagulation was not associated with clot resolution or prevention of PTS. Conclusion: TBI therapy is closely linked to the development of DVT. Coagulopathy on admission is associated with hypercoagulability in the postinjury period, suggesting a patient phenotype with systemic coagulation dysregulation. Treatment was not associated with improved VTE outcomes, suggesting that pediatric protocols should emphasize VTE prevention and prophylaxis strategies.